Genetic Programming by Nitric Oxide-Sensing Gene Switch System in Tumor-Targeting Bacteria - Yeshan Qin; Sung-Hwan You; Ying Zhang; Akhil Venu; Yeongjin Hong; Jung-Joon Min (Biosensors, 2023)
Recent progress in synthetic biology has enabled bacteria to respond to specific disease signals to perform diagnostic and/or therapeutic tasks. Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) colonization of tumors results in increases in nitric oxide (NO) levels, suggesting that NO may act as a candidate inducer of tumor-specific gene expression. The present study describes a NO-sensing gene switch system for triggering tumor-specific gene expression in an attenuated strain of S. Typhimurium. The genetic circuit was designed to sense NO via NorR, thus initiating the expression of FimE DNA recombinase. This was found to lead sequentially to the unidirectional inversion of a promoter region (fimS), which induced the expression of target genes. Target gene expression in bacteria transformed with the NO-sensing switch system was triggered in the presence of a chemical source of NO, diethylenetriamine/nitric oxide (DETA/NO) in vitro. In vivo results revealed that the gene expression is tumor-targeted, and specific to NO generated by inducible nitric oxide synthase (iNOS) after S. Typhimurium colonization. These results showed that NO was a promising inducer to finely tune the expression of target genes carried by tumor-targeting bacteria.